Fatty acids composition of kidneys under rat exposure to fungicides - S. V. Khyzhnyak; S. V. Midyk; О. В. Dovbysh; V. I. Korniyenko (The Ukrainian Biochemical Journal, 2025)
Most fungicides belong to the class of triazoles, of which tebuconazole and triadimefon are the most commonly used. Exposure to pesticides is accompanied by negative consequences for vertebrates and humans. However, the potential toxicity of fungicides is not well understood. The aim of the study was to estimate the fatty acids (FAs) composition of kidney total lipids after exposure of Wistar han rats to two fungicide preparations, one containing tebuconazole alone, the other tebuconazole + triadimephone. Animals were administered a single oral dose of fungicides (600 and 1200 mg/kg). After 14 days, the animals were decapitated and kidneys were used in the studies. FAs methyl esters were determined on a Trace GC Ultra gas chromatograph (USA) with the flame ionization detector. No qualitative changes in the FAs profile of the total kidney lipids after fungicides administration as compared to the control were detected, but the redistribution in the content of individual FAs was observed. The relative content of saturated fatty acids increased, while that of monounsaturated fatty acids, in particular oleic acid (C18:1ω9), decreased. An increase in the content of long-chain polyunsaturated fatty acids, in particular docosahexaenoic (C22:6ω3) and arachidonic (C20:4ω6) acids, as well as the value of the ratio ω3/ω6, was revealed. The effect of the combined fungicides was found to be more pronounced. The results indicate metabolic shift in the FAs profile of total kidney lipids in the dynamics after exposure to fungicides.